KARAKTERISTIK MENARA PENDINGIN DENGAN BAHAN ISIAN TALI IJUK - Johanes, Susanto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
In this study the characteristics of a water cooling tower with palm fibre as the packing material have been investigated experimentally. The experiments were carried out in a rectangle glass tower of 81 cm2 cross sectional area and 100 cm height. The packing used was constructed of 8 palm-fibre ropes (of about 0,6 cm diameter), zigzag and cross of water flow, and then it placed above the stainless steel support on the tower bottom. There were two type of packing i.e. 21,7.10-4 and 28,3.10-4 kg weigh of rope every m3 volume of the packing. The experimental results show that the increasing of the water inlet temperature and packing height causes the increasing of the tower characteristic . Mean while the increasing of the water/air mass flow rate ratio causes the decreasing of the tower characteristic.The tower characteristics is as a function of the investigated variables which expressed as: NTU = 165,24.10-3 (mw/ma)-0,999 (Z)0,5343 (Twi)0,1429 . It is for 21,7.10-4 kg/m3 of the specification of the packing material, with the relative error of 6,1 %, and NTU = 3,35.10-3 (mw/ma)-0,995 (Z)0,5050 (Twi)1,1643. It is for 28,3.10-4 kg/m3 of the specification of the packing material, with the relative error of 5,5 %.These equations are valid for the range variables, they are mw/ma of 4,46 – 9,48, Z of 30 – 90 cm, Twi of 50 – 60 oC. The mean effectiveness of the heat transfer were calculated to be 24,8 % and 25,9 %, respectivally for 21,7.10-4 and 28,3.10-4 kg/m3 of the specifications of the packing material.